Bolshevik Revolution and Disintegration of Soviet/Russian Historical Space in Central Asia. (3rd July 2019) - Shlapentokh, Dmitry
ABSTRACT: With disintegration of Soviet space, the historical narrative also changed. This could well be seen in Central Asia. Here, several narratives emerged.